Intravenous injection of a lentiviral vector encoding NY-ESO-1 induces an effective CTL response. - Palmowski, M; Lopes, L; Ikeda, Y; Salio, M; Cerundolo, V; Collins, M (2004)
Lentiviral vectors can efficiently transduce a variety of nondividing cells, including APCs. We assessed the immunogenicity of a lentiviral vector encoding the melanoma Ag NY-ESO-1 in HLA-A2 transgenic mice. Direct i.v. injection of NY-ESO-1 lentivirus induced NY-ESO-1(157-165)-specific CD8(+) cells, detected ex vivo with an A2/H-2K(b) chimeric class I tetramer. These NY-ESO-1(157-165)-specific CD8(+) cells could be expanded by boosting with an NY-ESO-1 vaccinia virus and could kill NY-ESO-1(157-165) peptide-pulsed targets in vivo. Such direct lentiviral vector injection was similar in potency to the injection of in vitro-transduced dendritic cells (DC). In addition, human monocyte-derived DC transduced by the NY-ESO-1 lentivirus stimulated an NY-ESO-1(157-165)-specific specific CTL clone. These data suggest that direct lentiviral transduction of DC in vivo might provide a powerful immunotherapeutic strategy.